A INTERPRETAÇÃO-APLICAÇÃO DO DIREITO NA CONSTRUÇÃO DA RESPOSTA CORRETA - Lima, Lucas Rodrigues (2020)
With a view on the problem of its concrete implementation, the present essay has as its object the most fundamental institute, in absolute, of the Law: the norm. In spite of this, call into question our on preconceptions, to once again, turn our eyes to w